Hubungan efek samping OAT dengan motivasi pasien TB paru untuk melanjutkan pengobatan - Elisabeth Wahyu Savitri; Usu Sius; Martinus Sudarso (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2021)
Motivation to follow up on the intensive phase treatment with occurrence side effects of anti-tuberculosis drugs (ATD) among patients with pulmonary tuberculosis Background: Tuberculosis (TB) is an infectious disease caused by the bacterium mycobacterium tuberculosis, which attacks various organs, especially the lungs. Transmission of TB disease through the air from droplets of infected patients. The main reason for treatment failure is the patient does not want to take medication regularly. Pulmonary TB cases in west kalimantan were not only contributed by new patients (97.5%) but also re-treatment patients (2.5%) in 2015. TB patients in sanggau district in 2011 were 390 people. There were only 39 patients with pulmonary TB who managed to get treatment in the work area of the damai center health center in 2017, while most were unsuccessful.Purpose:To find out the relationship between Motivation to follow up on the intensive phase treatment with occurrence side effects of anti-tuberculosis drugs (ATD) among patients with pulmonary tuberculosisMethod: A quantitative approach with a case study research strategy. The sample in the study was 39 respondents. The data obtained were then analyzed using the chi square test.Results: There was a relationship between itching (p value = 0.005), pain in the joints (p value = 0.018), reddish urine (p value = 0.001), nausea (p value = 0.000), impaired vision (p value = 0.001), and abdominal pain / hearTBurn (p value = 0.000) after taking oat with the motivation of pulmonary TB patients to continue treatment. On the other hand, there was no relationship between lack of appetite (p value = 0.055), dizziness (p value = 0.345), headache (p value = 0.257), and tingling (p value = 0.795) after taking oat with motivation. Pulmonary TB patients to continue treatment.Conclusion: There is a relationship between itching, pain in the joints, red urine, nausea, impaired vision, and abdominal pain after drinking oatsKeywords: Motivation; Follow up; Intensive phase treatment; Occurrence; Side effects of anti-tuberculosis drugs (ATD); Patients; Pulmonary tuberculosisPendahuluan: Tuberkulosis (TB) adalah penyakit infeksi menular yang disebabkan bakteri mycobacterium tuberculosis, menyerang berbagai organ, terutama paru - paru. Penularan penyakit TB melalui udara dari droplet pasien terinfeksi. Alasan utama gagal pengobatan adalah pasien tidak mau minum obat secara teratur. Kasus TB paru di kalbar tidak hanya disumbang oleh pasien baru (97,5%) tetapi juga pasien pengobatan ulang (2,5%) di tahun 2015. Penderita TB di kabupaten sanggau tahun 2011 sebanyak 390 orang. Penderita TB paru yang berhasil melakukan pengobatan di wilayah kerja puskesmas pusat damai tahun 2017 hanya 39 orang, sedangkan sebagian besar tidak berhasil.Tujuan: Mengetahui hubungan efek samping OAT dengan motivasi pasien TB paru untuk melanjutkan pengobatanMetode: Desain penelitian menggunakan pendekatan kuantitatif dengan strategi penelitian case study research. Sampel dalam penelitian 39 orang. Data yang diperoleh kemudian dianalisis menggunakan uji chi square.Hasil: Ada Hubungan antara rasa gatal (p value = 0,005), rasa nyeri pada persendian (p value = 0,018), urine berwarna kemerahan (p value = 0,001), rasa mual (p value = 0,000), penglihatan terganggu (p value = 0,001), dan rasa sakit perut / sakit ulu hati (p value = 0,000) setelah minum oat dengan motivasi pasien TB paru untuk melanjutkan pengobatan. Sebaliknya, tidak ada hubungan antara rasa kurang nafsu makan (p value = 0,055), rasa pusing (p value = 0,345), rasa sakit kepala (p value = 0,257), dan rasa kesemutan (p value = 0,795) setelah minum oat dengan motivasi pasien TB paru untuk melanjutkan pengobatan.Simpulan:Ada Hubungan antara rasa gatal, rasa nyeri pada persendian,urine bewarna kemerahan, rasa mual, penglihatan terganggu, dan rasa sakit perut setelah minum OAT